Complement activation assessed by the plasma terminal complement complex and future risk of venous thromboembolism - Høiland, Ina Isabella; Liang, Robin Amanda; Brækkan, Sigrid Kufaas; Pettersen, Kristin; Ludviksen, Judith K; Latysheva, Nadezhda; Snir, Omri; Ueland, Thor; Hindberg, Kristian; Mollnes, Tom Eirik; Hansen, John-Bjarne (Journal of Thrombosis and Haemostasis, 2019)
This is the peer reviewed version of the following article: Høiland, I.I., Liang, R.A., Brækkan, S.K., Pettersen, K., Ludviksen, J.K., Latysheva, N. . Hansen, J.-B. (2019). Complement activation assessed by the plasma terminal complement complex and future risk of venous thromboembolism. Journal of thrombosis and haemostasis, 17 (6), 934-943, which has been published in final form at https://doi.org/10.1111/jth.14438. This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Use of Self-Archived Versions. Background - It remains uncertain whether activation of the complement system, assessed by the soluble terminal C5b‐9 complement complex (plasma TCC), is associated with future risk of incident venous thromboembolism (VTE). Objectives - To investigate the association between plasma levels of TCC and future risk of incident VTE in a nested case‐control study, and to explore genetic variants associated with TCC using protein quantitative trait loci analysis of exome sequencing data. Methods - We sampled 415 VTE cases and 848 age‐ and sex‐matched controls from a population‐based cohort, the Tromsø study. Logistic regression models were used to calculate odds ratios with 95% confidence intervals for VTE across quartiles of plasma levels of TCC. Whole exome sequencing was conducted using the Agilent SureSelect 50 Mb capture kit. Results - The risk of VTE increased across increasing quartiles of plasma TCC, particularly for unprovoked VTE. Participants with TCC in the highest quartile (>1.40 complement arbitrary units/mL) had an odds ratio for unprovoked VTE of 1.74 (95% confidence interval: 1.10–2.78) compared with those with TCC in the lowest quartile (≤0.80 complement arbitrary units/mL) in analyses adjusted for age, sex, and body mass index. A substantially higher risk for VTE was observed in samples taken shortly before VTE event. We found no association between genome‐wide or complement‐related gene variants and plasma levels of TCC. Conclusions - We found that ...